ANALISIS KINERJA PERUSAHAAN DENGAN MENGGUNAKAN KONSEP BALANCED SCORECARD PADA PT. BUANA ARGA PALEMBANG - Ernawati . (Fakultas Ekonomi Universitas Tridinanti Palembang, 2015)
ABSTRACTÃ‚Â The purpose of this research is to know the performance of PT Buana Arga Palembang if measured using the Balanced Scorecard concept which includes a financial perspective, the customer perspective, the perspective of internal business processes and the learning and growth perspective. During this corporate performance measurement conducted by PT. Buana Arga Palembang only sourced from the company's financial information only.. Performance measurement results of PT. Buana Arga Palembang with the use of the Balanced Scorecard concept, it can be concluded that the first regular financial perspective, are said to be good because if compared to the previous year has increased: both, the perspective of the customer have been good but the level akuisasi customers has decreased: third, the internal business processes perspective shows the good performance of innovation conducted and services that have been provided to customers: fourth, the learning and growth perspective for employee productivity showed a good performance but to employee satisfaction levels are still less well resulting in the company's performance in maintaining employees very badly.Ã‚Â Keyword : Balanced Scorecard